Physical culture as a key to post-injury recovery in sports: Methods and future perspectives - Olesia Kholodova; Oksana Yudenko; Oksana Konovalenko; Odnovorchenko Igor; Veronika Doroshenko (Sport TK, 2025)
Sports injuries are a significant concern affecting both health and athletic performance, especially among adolescents, whose participation in organized sports continues to increase. This study explored the role of physical culture in post-injury recovery within a sports context, with a particular focus on adolescent athletes. Using content analysis and elements of grounded theory, the research examined current best practices and practical rehabilitation techniques. The findings indicated that the high incidence of sports-related injuries among adolescents is closely linked to their physiological development, as their musculoskeletal systems are still maturing. The study presented a classification of the most common injuries in this age group and highlights the growing demand for adolescent physical therapy due to rising injury rates. Based on systematic reviews, meta-analyses, and empirical studies, the results demonstrated that physical culture-based exercises and integrative rehabilitation programmes offer substantial benefits for recovery—particularly from concussions, spinal cord injuries, and knee injuries. As a key contribution, the study proposed a conceptual model outlining the relationship between components of effective integrative rehabilitation training programmes for adolescents, grounded in the principles of physical culture.